Alternative Dispute Resolution Model in the AJB Bumiputera Life Insurance Company of Purwokerto in Shari'ah Perspectives - Triana, Nita (Universitas Islam Negeri Raden Intan Lampung, 2018)
Resolution of disputes by way of litigation always takes a long time, expensive and results in a win and lose solution. Therefore resolution outside the court( non-litigation) is an alternative choice. This study analyses the resolution of insurance disputes using several methods or models outside the Court. This research is non-doctrinal legal research, with a socio-legal approach. It analyses a settlement model used by of Life Insurance AJB Bumiputera Purwokerto in the event of default of the insured/customer premium and the customer’s insurance claim against the company. The settlement involves several stages, first, by means of consultation and negotiation, second by means of mediation involving OJK (Financial Services Authority) as a neutral mediator, and the last, by means of conciliation and arbitration. In the perspective of Islamic law, this solution model is similar to the concept of sulh, a type of disputes resolution in which the conflicting parties drive to settle their dispute peacefully.